2014
DOI: 10.1016/j.conbuildmat.2014.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale fire testing and numerical modelling of the transient thermo-mechanical behaviour of steel-stud gypsum board partition walls

Abstract: In this paper, the authors present experimental observations and results of full scale standard fire tests as well as thermo-mechanical sequentially coupled finite element simulations on partition walls. A procedure for carrying out numerical simulation of the coupled-thermo-mechanical behaviour is proposed. The numerical models presented for predicting behaviour during fires were calibrated and verified by full scale fire testing.The test wall was constructed using steel C-section studs with gypsum boards fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…The project was supported by multinational manufacturers of plasterboards and steel doors systems. The first phase, which was previously reported by Nassif et al , was concerned with the fire behaviour of partition wall systems without inclusion of a door.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The project was supported by multinational manufacturers of plasterboards and steel doors systems. The first phase, which was previously reported by Nassif et al , was concerned with the fire behaviour of partition wall systems without inclusion of a door.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of steel‐stud gypsum‐faced walls during exposure to fires was investigated by a number of researchers . Such research efforts were concerned with the behaviour of such walls without the inclusion of doors in the tested walls.…”
Section: Introductionmentioning
confidence: 99%
“…According to the related researches made by Mansour et al [23], the values of the specific heat, thermal conductivity, and density of PVC are 900 J/kg°C, 0.16 W/m°C, and 1380 kg/m 3 , respectively. In this research made by Nassif et al [15], it presents some material property parameters related to mineral wool. Combining the specifications of mineral wool used in this research, the specific heat, respectively, is 840 J/kg°C and thermal conductivity increases as the temperature rises [24], as shown in Table 1.…”
Section: Parameter Settingmentioning
confidence: 99%
“…In addition, more and more numerical simultaneous aided researches in building field are processed by making use of CFD. For example, Collier and Buchanan [13] presented the prediction model for fire resistance of drywall by the finite element method; Do et al [14] came up with that the thermal conductivity of porous material is mainly related to the thermal conductivity of its components and spatial arrangement of its complex structure by formula, microstructure observation, and experiments; Nassif et al [15] presented the comparison of thermal conductivity of a dry gypsum board wall by the standard fire experiment and by numerical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…In recent research studies, SAFIR and Abaqus were extensively used and are the most commonly used FE software to investigate the thermal performances of LSF wall systems. The information related to these studies can be found in Nassif et al (2014), Keerthan and Mahendran (2012), Shahbazian and Wang (2013) and Feng et al (2003).…”
Section: Introductionmentioning
confidence: 99%